Young ones having younger ones: Adolescent mothers’ repeated pregnancy experiences in the Philippines - Adreal Denver Monterona (Universitas Trunojoyo Madura, 2020)
Many adolescents in the Philippines are not only getting pregnant under the age of 20 but are also having repeated pregnancies. Several local studies have determined the prevalence and the correlates of repeated pregnancies among Filipino adolescents, but the qualitative contexts in which these pregnancies are occurring are unclear yet are important for program development. This paper discusses some qualitative data drawn from experiences of youth who have had repeated pregnancies as a result of a qualitative study that employed the phenomenological and the narrative methodological approach. The study made use of data collected through individual in-depthinterviews with adolescents from the province of Pampanga, Philippines who have experienced more than one pregnancy from ages 15 to 19. Overall themes on the experiences of young mothers include positivity amid within the negativity and old connections, new unions. Found to be both a biological and social phenomenon, repeated adolescent pregnancy heightens both personal and social experiences of the young mother while it involves gender, forming and rebuilding of families as well as local context, and as such validates the need for further research.